Cancer awareness among adolescents in Irish schools: A cross-sectional study. - Stephanie M Lawrence; Mohamad M Saab; Serena FitzGerald; Josephine Hegarty (PLoS ONE)
Purpose The aim of this study was to assess adolescents' awareness of cancer signs and symptoms, cancer risk factors, cancer screening programmes, and perceived barriers to seeking medical advice. Methods A cross-sectional survey was conducted using an adapted version of the adolescent cancer awareness tool which was originally modified from the Cancer Awareness Measure (CAM) (Version 2.1). The sample included 474 adolescents aged 15 to 18 years recruited from nine Irish schools between November 2021 and May 2022. Results Awareness of cancer warning signs and symptoms was low when open-ended (recall) questions were used and relatively high for closed (recognition) questions. Unexplained lump or swelling was the most frequently identified cancer symptom. The least reported were difficulty swallowing and a sore that does not heal. Smoking was the most reported cancer risk factor. The least reported were not eating enough fruit and vegetables, a diet high in fat, and infection with viruses. Generally, females had greater awareness than males. The greatest barrier to seeking help was "worry about what the doctor might find" and the least reported barrier was "I don't feel respected by the doctor." Conclusions Overall recognition of symptoms or risk factors of cancer was higher than recall. Several modifiable barriers to medical help-seeking were identified. Findings from this study suggest further exploration using a qualitative approach to investigate the factors influencing adolescents' cancer awareness and barriers to help-seeking.